The Quaternary fossil assemblage of Layang Mawas Cave (Merapoh, Pahang) in Peninsular Malaysia: context, formation, composition and age constraints - Ros Fatihah Muhammad; Lim Tze Tshen; Mathieu Duval; Virginia Martínez-Pillado; Jian-xin Zhao; Clément Zanolli (Geobios, 2026)

New dating results at Incarcal‐I (Spain) shed light on the exceptionally rich late Early Pleistocene fossil record of the Iberian Peninsula - Mathieu Duval; Oriol Oms; Bienvenido Martinez‐Navarro; Rainer Grün; Isaac Rufí; María Prat‐Vericat; Sergio Ros‐Montoya; Maria Patrocinio Espigares; Joan Madurell‐Malapeira (Journal of Quaternary Science, 2026)
More than five decades after the first report of fossil remains found in a limestone quarry near Crespià, NE Spain, we provide here the first dating results for the palaeontological assemblage from Incarcal‐I, one of the various fossil‐rich sinkholes identified at the locality that has yielded ~2,000 remains representing at least 15 taxa of large mammals. Palaeomagnetism in conjunction with combined U‐series and electron spin resonance (ESR) dating of fossil teeth consistently constrain the age of Incarcal‐I to the latest part of the Early Pleistocene. Specifically, with palaeomagnetic results showing reverse magnetic polarities for the large majority of the samples and no indisputable evidence of normal polarity in the stratigraphic succession, the deposits may be reasonably correlated to the Matuyama Chron (2.61–0.77 Ma), thus providing a minimum age constraint of 0.77 Ma for the sedimentary infill. Additionally, direct dating of two fossil teeth of Hippopotamus antiquus using the most advanced analytical procedures, through a combination of unusually high sampling density ( n = 17) for bulk ESR and U‐series analyses and high‐resolution laser ablation Inductively Coupled Plasma‐Mass Spectrometry (ICP‐MS) analyses, yields a mean age of 862 ± 52 ka (1σ). Interestingly, the data set collected shows the exceptionally high spatial homogeneity of the ESR and U‐series data across dental tissues and of the natural radioactivity of the sedimentary environment. Furthermore, the uncertainty around the uranium uptake modelling carries very little weight in the age calculation, which is unusual for such old fossil teeth. Consequently, this set of evidence supports the robustness and reliability of the ESR chronology, adding a new solid chronological tie point for biochronological inferences. In summary, the various lines of evidence available enable confident positioning of Incarcal‐I in the latest part of the Early Pleistocene, that is, somewhere between the end of the Jaramillo Subchron (1.01 Ma) and the Matuyama–Brunhes boundary (0.77 Ma). The numerical dating results indicate that the fossil assemblage of Incarcal‐I is coeval with those from other well‐constrained key Spanish localities such as Atapuerca Gran Dolina TD4‐6, and Vallparadís Station EVT7, highlighting the overall exceptional density of the Iberian fossil record between ~0.8 and ~1.0 Ma. Finally, a critical evaluation of the existing age constraints available for the Calabrian (1.80–0.77 Ma) fossil localities of the Iberian Peninsula is also proposed here, with a first tentative classification of the sites into four main categories (A to D) based on the robustness and precision of their chronostratigraphic framework.

Refining the chronology of Middle/Late Pleistocene fossil assemblages in the Argentine Pampas - Jose Luis Prado; Mathieu Duval; Martina Demuro; Francisco Javier Santos-Arévalo; María Teresa Alberdi; Rodrigo L. Tomassini; Claudia I. Montalvo; Ricardo Bonini; Cristian M. Favier-Dubois; Sallie Burrough; Szilvia Bajkan; Germán M. Gasparini; et al. (Quaternary Science Reviews, 2024)

Extended-range luminescence and ESR dating of Iberian fluvial terraces (Duero and Guadiana basins) associated with the Lower Palaeolithic sites of La Maya I, II, III, Burganes and Albalá (west-central Spain) - Martina Demuro; Lee J. Arnold; Mathieu Duval; Alicia Churruca Clemente; Manuel Santonja; Alfredo Pérez-González (Quaternary Geochronology, 2024)

Re-examining the earliest evidence of human presence in western Europe: New dating results from Pirro Nord (Italy) - Mathieu Duval; Lee J. Arnold; Jean-Jacques Bahain; Josep M. Parés; Martina Demuro; Christophe Falguères; Qingfeng Shao; Pierre Voinchet; Julie Arnaud; Claudio Berto; Gabriele Luigi Francesco Berruti; Sara Daffara; et al. (Quaternary Geochronology, 2024)

Persistent headaches one year after bacterial meningitis: prevalence, determinants and impact on quality of life - Rémi Nguyen Van; Sarah Tubiana; Thomas De Broucker; Joseph Cédric; Carine Roy; Marie-Caroline Meyohas; Thierry Prazuck; Catherine Chirouze; Bruno Hoen; Xavier Duval; Matthieu Revest; Bruno Mourvillier; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2023)

The dawn of the Late Villafranchian: Paleoenvironment and age of the Pantalla paleontological site (Italy; Early Pleistocene) - Marco Cherin; Giorgio Basilici; Mathieu Duval; Qingfeng Shao; Mark J. Sier; Josep M. Parés; Elsa Gliozzi; Ilaria Mazzini; Donatella Magri; Federico Di Rita; Dawid A. Iurino; Beatrice Azzarà; et al. (Quaternary Science Reviews, 2023)

On the age of Ain Hanech Oldowan locality (Algeria): First numerical dating results - Mathieu Duval; Mohamed Sahnouni; Josep M. Parés; Jian-xin Zhao; Rainer Grün; Salah Abdessadok; Alfredo Pérez-González; Abdelkader Derradji; Zoheir Harichane; Nacim Mazouni; Kamel Boulaghraief; Razika Chelli Cheheb; et al. (Journal of Human Evolution, 2023)

Fluvial response to Quaternary hydroclimate in eastern Africa: Evidence from Gona, Afar, Ethiopia - Gary E. Stinchcomb; Jay Quade; Naomi E. Levin; Nels Iverson; Nelia Dunbar; William McIntosh; Lee J. Arnold; Martina Demuro; Mathieu Duval; Rainer Grün; Jian-xin Zhao; Marie White; et al. (Quaternary Science Reviews, 2023)

First magnetostratigraphic results in the Aïn Beni Mathar-Guefaït Basin, Northern High Plateaus (Morocco): The Pliocene-Pleistocene Dhar Iroumyane composite section - Josep M. Parés; Hamid Haddoumi; Mathieu Duval; Hassan Aouraghe; Claudia Álvarez-Posada; Sila Pla-Pueyo; Alfonso Benito-Calvo; Antonio Rodríguez-Hidalgo; Jan Van der Made; Pedro Piñero; Jordi Agustí; Aïcha Oujaa; et al. (Geobios, 2023)

The challenge of dating early pleistocene fossil teeth by the combined uranium series–electron spin resonance method: the Venta Micena palaeontological site (Orce, Spain) - Mathieu Duval; Christophe Falguères; Jean‐Jacques Bahain; Rainer Grün; Qingfeng Shao; Maxime Aubert; John Hellstrom; Jean‐Michel Dolo; Jordi Agusti; Bienvenido Martínez‐Navarro; Paul Palmqvist; Isidro Toro‐Moyano (Journal of Quaternary Science, 2011)
The palaeontological site of Venta Micena (Orce, Andalusia, Spain) lies in the eastern sector of the Guadix–Baza basin, one of the best documented areas in Europe for Plio‐Pleistocene biostratigraphy. The combination of biochronological and palaeomagnetic results, combined with the radiometric data obtained for Atapuerca Sima del Elefante, indicated that the Venta Micena stratum was formed between the Jaramillo and Olduvai palaeomagnetic events, most likely between 1.22 and 1.77 Ma. Five fossil teeth from two outcrops (sites A and B) were selected to assess the potential of combined uranium series–electron spin resonance (US‐ESR) dating of Early Pleistocene sites. Although the US‐ESR results of the first outcrop showed a large scatter between the three teeth, the mean age of 1.37 ± 0.24 Ma can be considered a reasonable age estimate for Venta Micena. The mean ESR age of 0.62 ± 0.03 Ma obtained for site B seems to be a severe underestimation when compared with the independent age control. This underestimation is attributed to a relative recent U‐mobilization event that led to some U‐leaching. The results show that any ESR age calculations of old samples are extremely sensitive to variations in the measured 230 Th/ 234 U ratios in dental tissues. Although the results demonstrate that ESR can in principle be applied to Early Pleistocene sites, they also reveal the complexity of dating such old teeth. It is necessary to continue research in several directions, such as study of the behaviour of ESR signals in old teeth and understanding recent U‐mobilization processes, to improve the reliability of the combined US‐ESR dating method applied to Early Pleistocene times, a period for which the number of available numerical dating techniques is very limited. Copyright © 2011 John Wiley & Sons, Ltd.

Effects of access to preen gland secretions on mallard plumage - Mathieu Giraudeau; Camille Duval; Noel Guillon; Vincent Bretagnolle; Claude Gutierrez; Philipp Heeb (The Science of Nature, 2010)

Thaxtomin A induces programmed cell death in Arabidopsis thaliana suspension-cultured cells - Isabelle Duval; Viviane Brochu; Mathieu Simard; Carole Beaulieu; Nathalie Beaudoin (Planta, 2005)